2017
DOI: 10.1111/joim.12605
|View full text |Cite
|
Sign up to set email alerts
|

Arterial ageing: from endothelial dysfunction to vascular calcification

Abstract: Complex structural and functional changes occur in the arterial system with advancing age. The aged artery is characterized by changes in microRNA expression patterns, autophagy, smooth muscle cell migration and proliferation, and arterial calcification with progressively increased mechanical vessel rigidity and stiffness. With age the vascular smooth muscle cells modify their phenotype from contractile to ‘synthetic’ determining the development of intimal thickening as early as the second decade of life as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
163
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(185 citation statements)
references
References 128 publications
(146 reference statements)
5
163
1
16
Order By: Relevance
“…Inflammation and oxidative stress are the main disorders which contribute to impaired function of the vascular endothelium [1]. Cellular senescence, which is a natural process, being parallel t body aging, also happens in the endothelial cells and accelerates the formation of atherosclerotic changes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation and oxidative stress are the main disorders which contribute to impaired function of the vascular endothelium [1]. Cellular senescence, which is a natural process, being parallel t body aging, also happens in the endothelial cells and accelerates the formation of atherosclerotic changes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Statins are routinely used in various stroke etiologies as secondary preventions due to its its lipid-lowering, vasculoprotective, and pleiotropic effects, which might be of benefit for patients with VBC [26]. Subclinical endothelial dysfunction is present in senescent population, a fact that we can indirectly confirm by finding VBC in significantly older patients [2].…”
Section: Discussionmentioning
confidence: 73%
“…Atherosclerosis is a potentially modifiable driver of overall morbidity and mortality [1]. Arterial calcification is an integral part in the process of atherosclerosis and can be detected in up to 90% of atherosclerotic plaques [2,3]. Radiological presence and extent of calcification is hence used as a noninvasive marker for the burden of atherosclerosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent preclinical and clinical studies have shown that vascular calcification is inexorable pathological process leading to mechanical rigidity and stiffness of vascular wall, endothelial dysfunction, development and accelerating atherosclerosis even in the absence of established cardiovascular (CV) disease [1][2][3]. Ectopic calcification is represented by several mutually counteracting molecular mechanisms, i.e., oxidative stress, microvascular inflammation, immune cell-to-cell cooperation, accumulation of lipids and extracellular proteins, vascular reparative systems, and metabolic disorders [4][5][6].…”
Section: Osteopontin In Vascular Calcificationmentioning
confidence: 99%